Epidemiology and Short-Term Outcomes of Obstetrical Suspected COVID-19 Patient: A Cross-Sectional Study in a COVID Dedicated Hospital of Bangladesh (Journal of Preventive and Social Medicine, 2021)
Background: COVID-19 is defiantly most notifiable killing infectious disease in twenty-first century that to bring unprecedented deadly toll in human life. Many developing and under developing countries faces great challenges to provide treatment facilities to their country people. Pregnant women are not beyond that exception. Besides, they experience absence of sensible humanity that never happened in the history of recent past. Many of them risking their lives and they suffered premature delivery, IUD, Still birth, PPH and even death for unnecessary delay to reach and receive treatment due to social stigma about COVID-19.Methods: This study was conducted in Department of Obstetrics & Gynecology of COVID Dedicated Unit of Dhaka Medical College Hospital. 300 COVID-19 suspected obstetrical patients included conveniently. The study period was from July 2020 to August 2020. It was a prospective observational cross-sectional study. The study subjects were selected following convenience sampling technique.Results: In this study majority of the patient (62.2%) were in the age group 20-29, where age limit was 14 to 45 years. Majority of the patients (55.7%) was either Illiterate or could sign only. Around half (51.0%) of the patients had monthly family income